2022
DOI: 10.1016/j.ebiom.2021.103761
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous ChAdOx1 nCoV-19 and BNT162b2 prime-boost vaccination elicits potent neutralizing antibody responses and T cell reactivity against prevalent SARS-CoV-2 variants

Abstract: Background Heterologous COVID-19 vaccination regimens combining vector- and mRNA-based vaccines are already administered, but data on solicited adverse reactions, immunological responses and elicited protection are limited. Methods To evaluate the reactogenicity and humoral as well as cellular immune responses towards most prevalent SARS-CoV-2 variants after a heterologous ChAdOx1 nCoV-19 BNT162b2 prime-boost vaccination, we analysed a cohort of 26 clinic employees aged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 47 publications
8
94
1
1
Order By: Relevance
“… 19 Similarly, a small German study that compared an 8-week interval of prime-boost ChAdOx1/BNT-162b2 with homologous BNT-162b2/BNT-162b2 vaccination found significantly higher neutralization titers against alpha variant and equivalent neutralizing activities against beta and delta variants. 20 Our study adds to the growing evidence that heterologous ChAdOx1/mRNA-1273 produces better neutralizing activities against both the alpha and delta variants than homologous ChAdOx1/ChAdOx1 vaccination when administered at 4-weeks or 8-weeks apart. Consistently, the analysis of spike-specific T cells and associated cytokines showed that the heterologous ChAdOx1/mRNA-1273 and the homologous mRNA-1273/mRNA-1273 vaccination stimulated more spike-specific cytokine-producing CD4 + T cells and more cytokine secretion than the homologous ChAdOx1/ChAdOx1 vaccination.…”
Section: Discussionmentioning
confidence: 65%
“… 19 Similarly, a small German study that compared an 8-week interval of prime-boost ChAdOx1/BNT-162b2 with homologous BNT-162b2/BNT-162b2 vaccination found significantly higher neutralization titers against alpha variant and equivalent neutralizing activities against beta and delta variants. 20 Our study adds to the growing evidence that heterologous ChAdOx1/mRNA-1273 produces better neutralizing activities against both the alpha and delta variants than homologous ChAdOx1/ChAdOx1 vaccination when administered at 4-weeks or 8-weeks apart. Consistently, the analysis of spike-specific T cells and associated cytokines showed that the heterologous ChAdOx1/mRNA-1273 and the homologous mRNA-1273/mRNA-1273 vaccination stimulated more spike-specific cytokine-producing CD4 + T cells and more cytokine secretion than the homologous ChAdOx1/ChAdOx1 vaccination.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have demonstrated a brisk antibody response to the booster vaccination [2][3][4][5], with some titers even higher than post-infection levels [3]. Booster vaccination has been shown to be effective against several different SARS-CoV-2 variants, including the new Omicron variant [6][7][8], and tolerated well with minimal side effects [9]. Indeed, booster vaccination regimens have been beneficial in controlling the spread of SARS-CoV-2, with real-world analysis [10] showing that it can reduce the rates of COVID-19 by a factor of 11.3, and severe illness by a factor of 19.5.…”
Section: Introductionmentioning
confidence: 99%
“…In the global struggle to achieve and maintain efficient COVID-19 vaccine programs, heterologous vaccine regimens attract great interest [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. With tolerable safety [ 1 , 8 , 9 ], and both immunogenicity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 ] and effectiveness [ 15 , 16 , 17 , 18 , 19 , 20 ] exceeding that of homologous adenovector immunization, heterologous primary vaccination is as of 7 December 2021 recommended by European Medical Agency and European Centre for Disease prevention and Control [ 21 ]. However, more data on the duration of immune responses following heterologous primary vaccine protocols are needed [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%